Interaction of key process variables acting on the simultaneous adsorption of phenolics in binary solution: trend and optimization of adsorption - Leong, K.-Y. (Research and Reviews, 2017)
The interest of present study focuses on the optimization of key process variables in enhancing the simultaneous adsorption process of phenol and 4-chlorophenol (4-CP) from their binary solution using response surface methodology (RSM). The interactive effects of spherical activated carbon (SAC) dosage, pH of solution and contact time were statistically analyzed via central composite design (CCD) of batch assessments. The CCD derived models of phenol and 4-CP removals were statistically found providing a satisfactory approximation to the real system. Among the exploited process variables, contact time was classified by the models to contribute the least effect on simultaneous adsorption process of phenol and 4-CP. The gradual increase of pH would undermine the effectiveness of adsorption process, though the SAC dosage and contact time responded reversely. The systematic statistical consideration of process variables found the optimum interaction occurred at the contact time of 24 h, SAC dosage of 0.09 g and pH of 7 with the attainable adsorption capacities of phenol and 4-CP in the ranges of 47 to 49 and 88 to 93, respectively. Verification by experimental run was performed with phenol and 4-CP removals found at 49 and 92, respectively, which were in agreement with the CCD predicted values.